INOVASI AKSELERASI TAHFIDZ QUR’AN DENGAN METODE QOZMU (QIRA’AT. ZIYADAH, MURAJA’AH) SEBAGAI PROGRAM HIDDEN CURRICULUM DI SDI AL-MUNAWWARAH PAMEKASAN - Ummu Kulsum; Abd Haris (AHSANA MEDIA: Jurnal Pemikiran, Pendidikan dan Penelitian Ke-Islaman, 2023)
Al-Munawwarah Islamic Elementary School conducts accelerated training for tahfidz Qur'an using the Qozmu method. The Al-Qur'an memorization program was initially carried out using the classical method, but it turned out to be less than optimal so it was deemed necessary to have a new format so that students' memorization could increase. The research method in this study was qualitative with a descriptive type, the source of the data was the teachers at the research location and at the same time some of the students the researcher made as research informants. Data collection methods are interviews, field observations and documentation data analysis. Meanwhile, the results of the research show that the Koran teacher has made an innovation called the acceleration of the tahfidz Qur'an using the Qozmu method: 1) The process of innovation change using the accelerated tahfidz Qur'an using the Qozmu method is made into a hidden curriculum program, and 2) Adaptation of students and teachers in dealing with changes to innovations made by using accelerated tahfidz Qur'an with the Qozmu method. The findings are that students can accelerate with the Qozmu method, using three categories in its implementation, namely, Qira'at, Ziyadah and Murajaah. The implication of this research is as an enrichment material for teaching methods so that learning in the classroom becomes more varied and teachers and students are always active and active in carrying out the learning process so that in the end they get the results as expected.